(3QSGdI GdBOGH ddHQchjs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO aGYde Cf GdefGXQI EPG fbd NHQG adNUeg WdH GdUMI abW Ef de jYQagG hEf GOYGgG aGdOdjd hGdJfHjg cPdc aEf CJi Hg adg efY HYV ebOeGJg Ch cdg eLQOG Ch eY SfO s
(3BNQgG (B:s
(3Ke aj GKHGJj GdeefhYI hGdGfJbGd jJUhQ ddNUe GdefGbVI hGdfbV hGdeYGQVI hGdCNjQGf efGbVI HGdfSHI Edi GdOdjd dchfg dGHO ef TGgO hbS Ydi gPG Edi jfJgj Edi YLR CMOgeG hGddg CYdes
(3jJdhgG fbhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 61s
(3eYLe GdeDdajf (B3 / 176s
(3gOjI GdYGQajf (B2 / 252s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs